Do you know them? - Keller, Shana, 1977- (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2024)
Set in 1865, a young girl named Lettie saves her money so she and her uncle can place an advertisement to find the members of their family that were separated under slavery.